Peran SPMI dalam Meningkatkan Mutu Pendidikan di SMA - Nadilla Wahyu Apriliani; Najwa Asyita Amalia; Mochamad Ilham Ramadhan (Universitas Maritim AMNI Semarang, 2024)
This study examines the role of the Internal Quality Assurance System (SPMI) in improving the quality of education in Senior High Schools (SMA) in Indonesia. In addressing the challenges of globalization, SPMI has become a crucial instrument to ensure that educational institutions meet national standards sustainably. SPMI involves principals, teachers, and educational staff through steps such as quality mapping, planning, quality fulfillment implementation, as well as evaluation and the establishment of new standards. This process promotes continuous self-evaluation to help schools achieve their vision and mission. The study employs a literature review method with a qualitative descriptive approach. Data were collected from books, scientific journals, and relevant documents using specific keywords and inclusion criteria. Data analysis identifies common patterns regarding the implementation of SPMI, including its successes and challenges. The findings indicate that SPMI has the potential to enhance the quality of education, although its implementation faces obstacles, such as teachers’ limited understanding of national standards. This study provides insights into the factors contributing to the success and challenges of SPMI implementation and offers contributions to the development of policies and practices in education in Indonesia, particularly in improving the quality of secondary education.